Identification of dietary patterns of adolescents attending public schools - Lucinéia de Pinho; Marise Fagundes Silveira; Ana Cristina de Carvalho Botelho; Antônio Prates Caldeira (Elsevier, 2014)
Objective: to identify the dietary patterns of adolescents attending public municipal schools in Northern Minas Gerais, Brazil, and to test the association between these patterns and socioeconomic variables and nutritional status of the adolescents. Methods: this was an analytical, cross-sectional study with randomized sample of 474 adolescents of both genders, between 11 and 17 years of age, attending municipal public schools in the urban area of Montes Claros, MG, Brazil. The parents provided demographic and economic data. The nutritional status (body mass index - BMI) of the adolescents was determined at school, and their dietary habits were assessed though the administration of the Food Frequency Questionnaire for Adolescents (FFQA). Based on 26 categories extracted from FFQA, dietary patterns were determined using principal component analysis (PCA) and associated to anthropometric and socioeconomic factors using multiple regression analysis. Results: the three dietary patterns identified, "junk food," "healthy," and "traditional", explained 23.26%, 6.90%, and 5.24% of data variability, respectively. Adolescents with per capita family income exceeding half a minimum wage were more likely to consume the "junk food" pattern (OR = 1.66; 95% CI = 1.07-2.56), and overweight adolescents had lower chances of eating the "healthy" food pattern (OR = 0.56, 95% CI = 0.35-0.91). Conclusions: deviations from the "healthy" patterns were not associated to low income, but rather to bad eating habits in the studied population. Overweight adolescents did not adhere to the "healthy" dietary pattern, emphasizing the need for nutritional education among them. Resumo: Objetivos: identificar os padrões de consumo alimentar de adolescentes de escolas públicas do norte de Minas Gerais e testar a associação desses padrões com variáveis socioeconômicas e estado nutricional. Métodos: estudo analítico e transversal com amostra aleatória de 474 adolescentes de ambos os sexos, 11 a 17 anos de idade, matriculados do 6° ao 9° ano de escolas públicas municipais da zona urbana de Montes Claros, MG. Os pais forneceram informações demográficas e econômicas. Nas escolas, avaliou-se o estado nutricional dos adolescentes (índice de massa corporal - IMC) e investigou-se seus hábitos alimentares aplicando-se um Questionário de Frequência Alimentar para Adolescentes (QFAA). Com base em 26 categorias de alimentos extraídas do QFAA, aplicou-se uma análise fatorial de componentes principais (ACP) para identificar os padrões alimentares, que foram associados a fatores antropométricos e socioeconômicos por análise de regressão múltipla. Resultados: os três padrões alimentares identificados, "junk food", "saudável" e "tradicional", explicaram 23,26%, 6,90% e 5,24% da variabilidade dos dados, respectivamente. Adolescentes com renda familiar per capita superior a 1/2 salário mínimo apresentaram maior chance de aderir ao padrão "junk food" (OR = 1,66; IC 95% = 1,07-2,56), enquanto aqueles com excesso de peso possuíram menor chance de aderir ao padrão "saudável" (OR = 0,56; IC 95% = 0,35-0,91). Conclusões: desvios do padrão alimentar "saudável" não estão relacionados à baixa renda, mas sim aos maus hábitos alimentares da população estudada. Adolescentes com sobrepeso não aderiram ao padrão "saudável", reforçando a necessidade da implementação de educação nutricional junto aos mesmos. Keywords: Adolescents, Eating Behavior, Principal Component Analysis, Palavras-chave: Adolescentes, Padrões Alimentares, Análise de Componentes Principais